2018
DOI: 10.1111/ans.14825
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological profile of community‐acquired musculoskeletal infections: a study from Queensland

Abstract: The bacteriological profile in this study is consistent with European and Australian data. While the overall MRSA infection rate was low, it was much higher among hand infections and is comparable to reports from the USA. Flucloxacillin and cefazolin should be considered as the first line of antibiotic therapy for all cases. Vancomycin should be considered when MRSA is suspected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Some authors have suggested that these numbers for primary total joint arthroplasty are both underestimated and increasing [10]. Gram-positive pathogens are thought to cause most PJIs, with staphylococci topping the list [11]. Indeed, the prevalence of methicillin-resistant S. aureus (MRSA) and S. epidermidis (MRSE) is increasing [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested that these numbers for primary total joint arthroplasty are both underestimated and increasing [10]. Gram-positive pathogens are thought to cause most PJIs, with staphylococci topping the list [11]. Indeed, the prevalence of methicillin-resistant S. aureus (MRSA) and S. epidermidis (MRSE) is increasing [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Nineteen (10%) children were readmitted for surgery, whereas the rest had some form of sequelae in the follow-up period. Sequelae were more common if range of motion (ROM) was affected at onset (86 versus 63%; P # 0.05) or if WBC count was higher at admission (median [IQR]: 14,850 [10,,277] versus 13,410 [10,100-17,600]; P 5 0.012). The proportion of children with sequelae was greater with increasing age (n [%]: , 1 year: 22 [37]; 1-5 years: 18 (39); .…”
Section: Weeks)mentioning
confidence: 99%
“…[4][5][6][7][8] The worldwide incidence of SA is reportedly rising due to a combination of increased longevity, multi-comorbidity, iatrogenic complications and increasing use of immunomodulating therapies for chronic arthritis and other conditions over the last 25 years. [9][10][11][12] Based on the above, and the limited availability of comprehensive Australian data, 13,14 we investigated the frequency, underlying clinical characteristics and outcomes of incident SA of native joints in Western Australia (WA) for patients admitted to hospital for SA from 1990-2010, with follow-up extending to 2015.…”
Section: Introductionmentioning
confidence: 99%